Divine Determinism and the Problem of Hell - Stratton, Tim (Perichoresis, 2018)
Divine determinism, though affirmed by many Calvinists, implicates God in the decisions people make that ultimately damn them to the terrible destiny of hell. In this paper, the authors argue that this scenario is a problem for divine determinism. The article contends that determinism is inconsistent with God’s love and the Scriptures that explicitly state that God does not ‘desire’ anyone to go to hell. Even human love for others strongly suggests that God, who is ‘love’, will not determine anyone to hell. On the other extreme, those who argue for universalism, though appealing to Scripture, often do so with questionable exegesis.